Experimental study on steel wire mesh reinforced concrete slabs against close-in detonations - Li, Jun; Wu, C. (2017)
© 2017 Taylor & Francis Group, London. High performance and aesthetic appearance of a structural design is the motivation behind high strength concrete development. As a notable representative, high performance steel fibre reinforced concrete is characterized by a much higher compressive and tensile strength compared with conventional concrete, the low water-cement ratio effectively warrants a low porosity microstructure which in turn enhances its durability. In recent years, with threat from terrorism activities, protection of structures against malicious loads such like explosive detonation is attracting more public concern. Due to its excellent mechanical performance and energy absorption capacity, high performance steel fibre reinforced concrete can be used in the construction of key load-carrying components to mitigate the blast induced structural damage. In current study, slabs made of high strength concrete material are field tested under close-in detonations, different reinforcement schemes including steel fibre reinforcement and steel wire mesh reinforcement are used in the slab design. Comparisons are made with normal strength concrete slab. Brief discussion on the different slab design against blast loads are presented.